FOLFOX7 regimen in the first-line treatment of metastatic colorectal cancer - Koca, Doğan; Ünal, Olçun Ümit; Öztop, İlhan; Yılmaz, Uğur (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: We aimed to investigate the efficacy and tolerability of a FOLFOX7 regimen in the first-line treatment of metastatic colorectal cancer (mCRC) patients. Materials and Methods: Patients were evaluated in two groups. Group A did not receive any treatment before, and group B had metastasectomy or metastasectomy plus primary tumor resection. Results: In total, 132 mCRC patients had received FOLFOX7 regimen. The A group consisted of 117 (88.6%) patients, and group B consisted of 15 (11.4%) patients. In the A group, 52.1% had an objective response, 9.4% complete response, 42.7% partial response, 24.8% stable response, and 23.1% progression, and there was a 54.5% rate of primary tumor resection, 22.2% rate of metastasectomy, 80.7% rate of R0 metastasectomy, 19.1% rate of R1 metastasectomy, 15 (10-19) months median progression-free survival, and 32 (22-41) months median overall survival. In the B group, 40 (4-70) months median disease-free survival and 58 (21-94) months median overall survival were found. When toxicities were evaluated, grade 3/4 toxicity was observed in 35.6%. Grade 3/4 hematologic toxicity was the most frequently observed toxicity (29.5%). Conclusion: FOLFOX7 regimen was found to be an efficient and safe regimen for the first-line treatment of mCRC patients.